Differential effects of language attrition in the domains of verb placement and object expression - Flores, Cristina (2012)
This study investigates the differential effects of language attrition in two diverse linguistic domains: verb placement and object expression. Linguistic phenomena at the syntax - discourse interface, such as object expression, have been shown to be more vulnerable to attrition than narrow syntax properties, such as verb placement. This study aims to test this hypothesis by analysing spoken data from Portuguese-German bilinguals who have moved away from the dominant German environment. The results show that the speakers who have lost continued German input after the age of 11 exhibit difficulties regarding object expression in German but do not reveal any relevant syntactic deficits in the domain of verb placement.